Genomic anatomy of the specific reciprocal translocation t(15;17) in acute promyelocytic leukemia - Reiter, Andreas; Saußele, Susanne; Grimwade, David; Wiemels, Joseph L.; Segal, Mark R.; Lafage-Pochitaloff, Marina; Walz, Christoph; Weißer, Andreas; Hochhaus, Andreas; Willer, Andreas; Reichert, Anja; Büchner, Thomas; et al. (Genes, chromosomes & cancer, 2003)
The genomic breakpoints in the t(15;17)(q22;q21), associated with acute promyelocytic leukemia (APL), are known to occur within three different PML breakpoint cluster regions (bcr) on chromosome 15 and within RARA intron 2 on chromosome 17; however, the precise mechanism by which this translocation arises is unclear. To clarify this mechanism, we (i) assembled the sequence of RARA intron 2, (ii) amplified and sequenced the genomic PML-RARA junction sequences from 37 APL patients, and (iii) amplified and sequenced the reverse RARA-PML genomic fusion in 29 of these cases. Three significant breakpoint microclusters within RARA intron 2 were identified, suggesting that sequence-associated or structural factors play a role in the formation of the t(15;17). There was no evidence that the location of a breakpoint in PML had any relationship to the location of the corresponding breakpoint in RARA. Although some sequence motifs previously implicated in illegitimate recombinations were found in the microcluster regions, these associations were not significant. Comparison of forward and reverse genomic junctions revealed microhomologies, deletions, and/or duplications of either gene in all but one case, in which a complex rearrangement with inversion of the PML-derived sequence was found. These findings are consistent with the hypothesis that the t(15;17) occurs by nonhomologous recombination of DNA after processing of the double-strand breaks by a dysfunctional DNA damage-repair mechanism.
First published: 13 December 2002
Gesehen am 16.05.2022